2020
DOI: 10.1590/1806-9282.66.7.954
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neutrophil and neutrophil/lymphocyte ratio in coronary collateral developed patients with acute coronary syndrome

Abstract: SUMMARY OBJECTIVE Inflammation-related markers provide diagnostic and prognostic information for coronary artery disease and acute coronary syndrome. We aimed to compare neutrophil count and neutrophil/lymphocyte ratio (NLR) in acute coronary syndrome patients with coronary collateral development in our study. METHODS A total of 426 patients (102 unstable angina pectoris (USAP), 223 non-ST-elevation myocardial infarction (non-STEMI), 103 ST-elevation myocardial infarction (STEMI) were compared regarding he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
1
0
1
Order By: Relevance
“… 22 Interestingly, an elevated NLR, reflecting the balance between the innate and the adaptive immune responses, has been associated not only with the presence of CVD but also with short-term adverse outcomes, including mortality, in patients with CVD. 23 In accordance with previous reports, 24 , 25 we found higher levels of neutrophils and NLR in STEMI patients at admission compared with patients with stable angina. However, herein we showed that there was a significant decrease in neutrophil counts and NLR, mainly driven by a reduction in neutrophil counts, during hospitalisation in the tocilizumab arm compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
“… 22 Interestingly, an elevated NLR, reflecting the balance between the innate and the adaptive immune responses, has been associated not only with the presence of CVD but also with short-term adverse outcomes, including mortality, in patients with CVD. 23 In accordance with previous reports, 24 , 25 we found higher levels of neutrophils and NLR in STEMI patients at admission compared with patients with stable angina. However, herein we showed that there was a significant decrease in neutrophil counts and NLR, mainly driven by a reduction in neutrophil counts, during hospitalisation in the tocilizumab arm compared with placebo.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study, Mansiroglu et al (16) conducted a single-centered study of 426 patients who were admitted to Bolu Abant Izzet university hospital, to assess the relation between NLR and ACS. They realized that neutrophil and NLR were higher in NSTEMI patients that in unstable angina patients, also El Shafey et al (17) concord with our study that higher NLR counts for NSTEMI patients unlike lower NLR for unstable angina.…”
Section: Discussionsupporting
confidence: 87%
“…In this inflammatory process neutrophils play a central and enhance inflammatory process by many mechanisms like arachdonic acid pathway, by generating oxygen free radicals and with the help of hydrolytic enzymes 13,14 . Lymphocytes have the ability to suppress inflammation and decreased lymphocyte count is associated with poor cardiac outcome 15 Stress during myocardial infarction lead to lymphopenia because of catecholamine induced apoptosis and suppression of maturation of lymphocytes 16,17,18 . So white blood cell count, neutrophil count and neutrophil lymphocyte ratio are simple inexpensive, readily available measure that can be used to stratify high risk patients 19,20 .…”
Section: Discussionmentioning
confidence: 99%